Australian 'gayborhoods' and 'lesborhoods': a new method for estimating the number and prevalence of adult gay men and lesbian women living in each Australian postcode. Issue 11 (1st November 2020) - Callander, Denton; Mooney-Somers, Julie; Keen, Phillip; Guy, Rebecca; Duck, Tim; Bavinton, Benjamin R.; Grulich, Andrew E.; Holt, Martin; Prestage, Garrett
ABSTRACT: Gay men and lesbian women often demonstrate unique settlement patterns, forming what have been referred to as 'gayborhoods'. This study sought to provide the first postcode-level estimates of population size and prevalence of gay and lesbian people in Australia. Data on same-gender-partnered households from the Australian Census were combined with information from six different surveys conducted from 2011 to 2017. We estimated that in 2016 there were 132, 203 gay men (1.5% of adult males; 95% CI: 1.4–1.6) and 79, 931 lesbian women (0.9% of adult females; 95% CI: 0.8–1.0) in Australia. While many postcodes were sparsely populated by gay and lesbian people (40.1% had prevalences of <0.1%), 24.6% were moderately populated (prevalences in the 50-95th percentile) and 2.7% were highly populated (95th percentile). By jurisdiction, the Australian Capital Territory had the highest prevalences of gay men (2.1%; 95% CI: 2.0–2.2) and lesbian women (1.5%; 95% CI: 1.4–1.6). Although the majority of highly populated postcodes were found in major cities (83.7%), some were also found in regional and remote area (16.3%). This method can be applied in other countries to enhance populate estimates. The accompanying dataset can be used to guide service delivery, conduct geographically contextualised research and develop policies relevant to gay men and lesbian women in Australia.